Experimental Study on the Mechanical Properties of Reinforced Pervious Concrete - Lee, Ming-Gin; Wang, Yung-Chih; Wang, Wei-Chien; Chien, Hung-Jen; Cheng, Li-Chi (Buildings (Basel), 2023)
Pervious concrete (PC) has gained popularity as an environmentally friendly solution for mitigating the urban heat island effect and promoting sustainable construction. However, its lower compressive strength, attributed to its higher porosity required for permeability, poses challenges for withstanding heavy vehicle loads on pavements. Our study aims to improve the flexural strength of regular PC by adding advanced reinforcing materials like steel wire mesh or glass fiber mesh. This results in reinforced pervious concrete, referred to as RPC, which offers enhanced strength and durability. The primary objective of our research is to investigate the mechanical behavior of RPC, with a specific emphasis on essential design parameters such as PC elastic modulus, modulus of rupture, and stress–strain characteristics under both single and repeated loading conditions. Our findings reveal that the influence of repeated loading on the compressive strength and elastic modulus of PC pavement is negligible, as there are no significant differences observed between the two loading protocols. Notably, our statistical analysis indicates that the PC strength (fc′) averages around 15 MPa. Moreover, empirical formulas for the elastic modulus (Ec = 3072fc′) and modulus of rupture (fr = 0.86fc′) are derived from our research. Furthermore, our study establishes that the stress–strain behavior of PC closely aligns with the general concrete model proposed by a previous scholar, providing valuable insights into the material’s structural performance. These findings contribute to a better understanding of RPC’s mechanical properties and offer potential solutions for improving its suitability for heavier vehicular loads.